Study of nitrogenous substances formation during combustion of coal - Askarova, A.S.; Bolegenova, S.A.; Bolegenova, S.A.; Maximov, V.Yu.; Beketayeva, M.T. (Recent Contributions to Physics, 2017)
The process of burning coal fuel accompanied by complex physical and chemical processes that should been considered in the numerical study are paramount. An importance has the quality of combusted coal fuel. Coal rank depends on volatile substances, and outlet of harmful combustion products like carbon oxides, nitrogen and sulfur oxides and others. Nitric oxide formation in hydrocarbon flames occurs primarily through three mechanisms; thermal NO (the fixation of molecular nitrogen by oxygen atoms produced at high temperatures), fuel NO (the oxidation of nitrogen contained in the fuel during combustion), and prompt NO (the attack of a hydrocarbon radical on molecular nitrogen). Of these three mechanisms, fuel NO is by far the most significant source of NO in practical coal flames. In the work with the help of kinetic schemes of formation of nitrogenous substances was investigated Karaganda coal combustion process in the combustion chamber of the real energy boiler. Based on these results and their verification it had been offered the most appropriate mechanism of NOx formation for the base of numerical calculations at any thermal power stations that using high ash content Kazakh coal. The results of such research work may develop technical and constructional proposals for optimization of combustion processes.
Keywords: aerodynamics of flow, fuel combustion, kinetic mechanism, modeling, NOх, nitrous oxides, heat mass transfer